"Det skal råtne". Materialbruk og retorikk i nyere samisk arkitektur - Haugdal, Elin Kristine (Universitetsforlaget, 2013)
This article investigates public architecture in Sápmi from the 1970s until today, with particular emphasis on building materials and their discourse. Although the materials chosen for clothing or for revealed construction follow Nordic and inter¬national architectonic trends, the wood, stone, concrete and glass are ascribed a set of meanings to fit the Sami context. The question is to what degree these materials mediate conventional and even stereotypical understandings of Saminess, or produce awareness of new Sami architecture and identity.